Overstuffing the patellofemoral compartment in total knee arthroplasty: a systematic review - Marco Gupton; Jordan E Johnson; G Robert Cummings; Chenthuran Deivaraju (EFORT Open Reviews, 2023)
Total knee arthroplasty (TKA) is generally considered a successful surgery, although 5–20% of individuals are unhappy with their outcome following surgery (1, 2), and approximately 5–10% will eventually go on to revision surgery within 10 years (3, 4). There are reports of up to 23% of patients experiencing of anterior knee pain (AKP) postoperatively (5, 6, 7). Loss of motion, decreased function, and pain are three causes of post-TKA AKP that are believed to be attributable to the anatomy and function of the patellofemoral joint (PFJ) (8, 9, 10, 11, 12, 13, 14, 15, 16). The dimensions of the PFJ are affected by the femoral implant position and size, as well as the position and size of the patellar prosthesis after resurfacing is performed (15, 17). PFJ overstuffing occurs as the amount of bone and cartilage resected is less than the thickness of the prosthesis replacing it (11, 12, 18). The anteroposterior PFJ size is altered by a combination of changes in the anterior patellar displacement (APD), anterior-posterior femur diameter (APFD), anterior femoral offset (AFO), and posterior femoral offset (PFO) (11, 12, 17, 18). There have been several biomechanical (19, 20, 21, 22, 23, 24, 25) and clinical papers suggesting the negative effects of PFJ overstuffing (11, 26, 27, 28, 29, 30, 31). In contrast, there have also been a number of biomechanical (20, 32) and clinical studies suggesting no effect on clinical outcomes when the amount of overstuffing is within reason (7, 15, 16, 18, 33, 34, 35). This study aims to systematically review all of the available literature to determine if PFJ overstuffing in TKA affects clinical outcomes.